Heavy Metals Contamination in Surface Water Due to Intensive Agricultural Chemical Use: A Case Study of the Hantu River in the Vicinity of Oil Palm Plantations, Banyuasin Sumatera Selatan Indonesia - Candra, Kalepi; Budianta, D.; Napoleon, A.; Antoni, M. (Journal of Ecohumanism, 2024)
Water pollution is a serious issue that requires immediate attention, especially when the water serves as a source for household activities. The consequences, such as health disorders or death, may occur if contaminated water is consumed continuously. Polluted water often contains various types of heavy metals. This study highlights changes in the water quality of the Hantu River, located near private oil palm plantations, focusing on the analysis of heavy metal contamination suspected to be present in the river water. The research was conducted by collecting water samples from the upstream and downstream sections of the river, followed by testing using the Atomic Absorption Spectrophotometry (AAS) method to measure heavy metal concentrations. The parameters assessed included heavy metals such as iron (Fe), manganese (Mn), cadmium (Cd), lead (Pb), mercury (Hg), and zinc (Zn). The results showed fluctuations in Fe and Zn contamination during the study period, while Mn and Hg contamination remained consistent each year. However, a startling finding was the concentration of Cd and Pb, which exceeded drinking water quality standards by 200%. This fact rendered the surface water unsuitable for consumption. It is suspected that the contamination occurred due to the use of materials for pest control (pesticides), weed control (herbicides), and the massive and continuous application of Palm Oil Mill Effluent (POME) during the 2019–2023 period. Regression models indicated a significant relationship between the use of pesticides, herbicides, and POME with contamination levels, accounting for 89.6% of Cd pollution and 92.3% of Pb pollution in the water. These findings demonstrate the impact of pesticides, herbicides, and POME on water quality concerning heavy metal pollution parameters. Therefore, managing the use of pollution sources and continuously monitoring water quality are essential to prevent and detect potential pollution in the future.